The Effectiveness of Cognitive Restructuring-based Group Counseling in Reducing Academic Stress among Generation Z Vocational High School Students - Dona Fitri Annisa; Prio Utomo; Tiara Agustine; Yahya Muhammed Bah; Adaobi Jennifer Iloakasia (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
Generation Z vocational high school students encounter complex academic and social pressures that frequently induce overwhelm and overachievement tendencies, thereby elevating their risk of academic stress. This study evaluated the effectiveness of cognitive restructuring-based group counseling in reducing academic stress among Generation Z students in a vocational high school context. Employing a mixed-methods approach with an explanatory sequential design, the study purposively selected nine tenth-grade students from the Fashion Department at SMKN 3 Cimahi who exhibited high levels of academic stress. Quantitative data were gathered using an academic stress questionnaire based on Gadzella’s theory and analyzed via the Shapiro-Wilk test and paired samples t-test. The findings revealed that the cognitive restructuring intervention significantly reduced academic stress, as evidenced by a mean score decrease from 75 (high category) to 45 (low category), with a p-value of 0.000 (t = 57.553; df = 8). These results indicate that cognitive restructuring-based group counseling serves as an effective, evidence-based guidance strategy, enabling Generation Z students to develop emotional regulation, adaptive cognitive patterns, and coping skills to mitigate academic pressures in vocational education